Extracorporeal Life Support for Cardiogenic Shock With Either a Percutaneous Ventricular Assist Device or an Intra-Aortic Balloon Pump. Issue 1 (January 2021) - Nakajima, Tomohiro; Tanaka, Yuki; Fischer, Irene; Kotkar, Kunal; Damiano, Ralph J.; Moon, Marc R.; Masood, Muhammad F.; Itoh, Akinobu
Abstract : Extracorporeal life support (ECLS) can result in complications due to increased left ventricular (LV) afterload. The percutaneous ventricular assist device (PVAD) and intra-aortic balloon pump (IABP) are both considered to be effective means of LV unloading. This study describes the efficacy of LV unloading and related outcomes with PVAD or IABP during ECLS. From January 2010 to April 2018, all cardiogenic shock patients who underwent ECLS plus simultaneous PVAD or IABP were analyzed. Forty-nine patients received ECLS + PVAD, while 91 received ECLS + IABP. At 48 hours, mean pulmonary artery pressure was significantly reduced in both groups [34 mm Hg to 22, p < 0.01; 32 mm Hg to 21, p < 0.01; ECLS + PVAD and ECLS + IABP group, respectively]. The two groups had similar 30 day survival rates [19 patients (39%) vs. 35 (39%), p = 0.56]. The ECLS + PVAD group had higher incidences of bleeding at the insertion site [11 (22%) vs. 0, p < 0.01] and major hemolysis [9 (18%) vs. 0, p < 0.01]. Both groups had improvement in LV end-diastolic dimension (61 ± 12 mm to 54 ± 12, p = 0.03; 60 ± 12 mm to 47 ± 10, p < 0.01), and LV ejection fraction (16 ± 7% to 22 ± 10, p < 0.01; 22 ± 12% to 29 ± 15, p = 0.01). Both ECLS + PVAD and ECLS + IABP effectively reduced pulmonary artery pressure and improved LV function. Bleeding at the PVAD or IABP insertion site occurred more frequently in the ECLS + PVAD group than the ECLS + IABP group ( p < 0.01). Nine patients (18%) in the ECLS + PVAD group experienced major hemolysis, while there was no hemolysis in the ECLS + IABP group ( p < 0.01). Careful considerations are required before selecting an additional support to ECLS. Abstract : Supplemental Digital Content is available in the text.